Effect of Disciplinary Duty and Career Development on The Task Commitment With The Motivation to Work As a Variable Intervening the Directorate of Police Air Police In West Sumatera Region - Rizal Sriwijaya; Ibadus Soim; Adril Muniza; Yulina Eliza (Universitas Batanghari, 2020)
This research aims to be aware of the Influence of task discipline and career development on the task commitment with the motivation to work as variable Intervening members of the Directorate of Police Air West Sumatera region as much as 91 people. Data collected through the dissemination of questionnaires to all populations that can be used for analysis purposes. Testing the hypothesis is done using data analysis technology through Path Anlysis. The results of Data analysis demonstrated that the task discipline and career development have significant effect on the task commitment next task discipline and career development have significant effect on work motivation as variable Intervening. Likewise, the work motivation also has significant effect on the task commitment. Variable Intervening motivation work is significant to the commitment of the task, further motivation work as a intervening between task discipline and task commitment, and motivation to work as a intervening relationship between career development and Task Commitment of the Directorate of West Sumatera Regional police. The magnitude of the influence of duty discipline, career development and work motivation affects the task commitment of 86.4%, while the remainder (100%-86.4% = 13.6%) is not included in this model.